The Media Literacy of Teenagers - Pierre Fastrez; Nathalie Lacelle; Julia Bihl; Eve Gladu; Eric Delamotte; Catherine Delarue-Breton; Christophe Ronveaux; Denise Sutter Widmer (Educare)
In this paper, we present the conceptual framework, objectives, and methodology of an interdisciplinary research program (2018–2022) on the media literacy competence of teenagers in French-speaking Belgium, Quebec, France, and Switzerland. The program is undertaken by researchers in four universities, one in each national context. Focusing on information search and multimodal production as core media literacy activities, this program develops a multi-level assessment method to measure media literacy competence at varying levels of complexity. Additionally, we relate task-based measures of competence with self-reported competence and practices and seek to document the influence of the students’ interpretation of the tasks contexts and purposes, their motivation and feeling of empowerment, and their collaborative practices on the exercise of their media literacy. Preliminary results reveal that students report substantially higher levels of competence in information search than in web production; however, this difference is reduced when students assess their ability to perform specific search-related or production-related actions. These results are discussed in light of the potential usefulness of the program for teachers and for curricular design.